Milk, Honey & Tomatoes - Kloer, Andre; Broos, Maaike (Netherlands, 2011)
On the fertile fields of the West bank, a young Palestinian boy grows up, knowing he will work for the rest of his life in the Jewish settlements, picking cherry tomatoes and dates that are sold in Europe as 'Made in Israel'.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films